Predictors of objective cough frequency in pulmonary sarcoidosis. Issue 5 (4th February 2016) - Sinha, Aish; Lee, Kai K.; Rafferty, Gerrard F.; Yousaf, Nadia; Pavord, Ian D.; Galloway, James; Birring, Surinder S.
Cough is a common symptom of pulmonary sarcoidosis. This study aimed to quantify cough frequency, and investigate its relationship with cough reflex sensitivity, pulmonary function and health status. 32 patients with pulmonary sarcoidosis were compared with 40 healthy controls. Cough reflex sensitivity to capsaicin, objective 24-h cough counts, cough-specific health status, cough severity and cough triggers were measured. The predictors of cough frequency in sarcoidosis were determined in a multivariate analysis. Objective cough frequency was significantly raised in patients with sarcoidosis compared with healthy controls (p<0.001) and patients with cough had an impaired health status. Patients with pulmonary sarcoidosis had a heightened cough reflex sensitivity compared with healthy controls (p<0.001). Only cough reflex sensitivity was significantly associated with objective cough frequency in multivariate analysis, explaining 42% of the variance (p<0.001). There was no association between cough frequency, lung function, number of organs involved, chest radiograph stage or serum angiotensin-converting enzyme levels. Cough is a common and significant symptom in patients with sarcoidosis. Ambulatory objective cough monitoring provides novel insights into the determinants of cough in sarcoidosis, suggesting that cough reflex sensitivity may be more important than lung function and other measures of disease severity, and this should be investigated further. Cough reflex hypersensitivity is an important determinant of objective cough frequency in sarcoidosis http://ow.ly/W4q9e